Peripheral skin cooling during hyper-gravity: hemodynamic reactions - Kagelmann, Niklas; Janke, David; Maggioni, Martina Anna; Gunga, Hanns-Christian; Riveros Rivera, Alain; Genov, Magdalena; Noppe, Alexandra; Habazettl, Helmut; Bothe, Tomas Lucca; Nordine, Michael; Castiglioni, Paolo; Opatz, Oliver (Frontiers in Physiology, 2023)
Introduction: Orthostatic dysregulation occurs during exposure to an increased gravitational vector and is especially common upon re-entering standard Earth gravity (1 g) after an extended period in microgravity (0 g). External peripheral skin cooling (PSC) has recently been described as a potent countermeasure against orthostatic dysregulation during heat stress and in lower body negative pressure (LBNP) studies. We therefore hypothesized that PSC may also be an effective countermeasure during hyper-gravity exposure (+Gz). Methods: To investigate this, we designed a randomized short-arm human centrifuge (SAHC) experiment (“Coolspin”) to investigate whether PSC could act as a stabilizing factor in cardiovascular function during +Gz. Artificial gravity between +1 g and +4 g was generated by a SAHC. 18 healthy male volunteers completed two runs in the SAHC. PSC was applied during one of the two runs and the other run was conducted without cooling. Each run consisted of a 10-min baseline trial followed by a +Gz step protocol marked by increasing g-forces, with each step being 3 min long. The following parameters were measured: blood pressure (BP), heart rate (HR), stroke volume (SV), total peripheral resistance (TPR), cardiac output (CO). Furthermore, a cumulative stress index for each subject was calculated. Results: +Gz led to significant changes in primary as well as in secondary outcome parameters such as HR, SV, TPR, CO, and BP. However, none of the primary outcome parameters (HR, cumulative stress-index, BP) nor secondary outcome parameters (SV, TPR, CO) showed any significant differences—whether the subject was cooled or not cooled. Systolic BP did, however, tend to be higher amongst the PSC group. Conclusion: In conclusion, PSC during +Gz did not confer any significant impact on hemodynamic activity or orthostatic stability during +Gz. This may be due to lower PSC responsiveness of the test subjects, or an insufficient level of body surface area used for cooling. Further investigations are warranted in order to comprehensively pinpoint the exact degree of PSC needed to serve as a useful countermeasure system during +Gz.